Secretory function of the vestibular nerve calyx suggested by presence of vesicles, synapsin I, and synaptophysin - Scarfone, E (J Neurosci, 1988)
Type I sensory hair cells of the vestibular epithelium are nearly completely ensheathed by an afferent nerve ending, the vestibular nerve calyx. We have recently reported that the nerve calyx, and, in particular, its apical portions surrounding the neck of the hair cell, are immunoreactive for synapsin I (Favre et al., 1986), a major membrane component of small synaptic vesicles of axonal endings. We have now found, by electron microscopy, that the same region of the calyx is densely populated by microvesicles morphologically similar to typical presynaptic small synaptic vesicles. Furthermore, we have established by light microscopy immunocytochemistry that this region of the calyx also contains a high concentration of synaptophysin, another well-characterized major component of small synaptic vesicle membranes. These results suggest that the upper portion of the calyx is equipped with the machinery that in presynaptic terminals is involved in the release of neurotransmitters and raise the possibility that the calyx, via secretion of neurotransmitterlike substances, might modulate the function of type I hair cells.